Islamists, Soldiers, and Conditional Democrats:: Comparing the Behaviors of Islamists and the Military in Algeria and Turkey - Ashour, Omar; Ünlücayakı, Emre (Journal of Conflict Studies, 2006)
ABSTRACT This article compares the responses of the Islamist political forces in Algeria under military pressure to their counterparts in Turkey, under similar duress. While the former rose in a revolt resulting in a violent civil war, the latter chose not to employ violent means and resorted instead to political activism. To understand this discrepancy in the behavior, we propose three independent variables: the ideological and structural differences between two major Islamist groups in Algeria and Turkey, namely the FIS and the RP, and the role of the military in the political-cultural context of both countries. A historical review of Islamic-oriented activism since the nineteenth century is provided in both case studies. This review highlights the empirical factors that shape the contemporary political cultures of Algeria and Turkey, and therefore affect the political attitudes of both the military and the Islamists in their respective countries.